Study of Charge Transfer Contribution to Surface-Enhanced Raman Scattering Activity of Cu\(_2\)O Nano-octahedral Substrate - Tran, Thu Trang; Vu, Xuan Hoa; Thi Thu Ha Pham,; Nguyen, Trong Nghia; Nguyen, Dac Dien (Communications in Physics, 2022)
In this study, a surface-enhanced Raman scattering (SERS) substrate based on an octahedral cuprous oxide (Cu2O) nanostructure to probe methylene blue (MB) molecules as an analyte chemical has been implemented. Octahedral Cu2O nanocrystals were synthesized by a novel hydrothermal process using only ethylene glycol as both a reductant and organic solvent. The characteristics of Cu2O nanocrystals were well recognized by scanning electron microscope (SEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), FTIR, and Raman spectroscopy. The mechanism of the SERS surface has been thoroughly investigated and has been shown to involve the contributions of both surface plasmon resonance and charge transfer effects. Using a simple collection rule for SERS bands, the portion of charge transfer processes was estimated to be about 46%.